2004
DOI: 10.1002/pbc.20156
|View full text |Cite
|
Sign up to set email alerts
|

Waiting times for cancer care in Canadian children: Impact of distance, clinical, and demographic factors

Abstract: Distance to treating center had no significant impact on waiting times for important diagnostic and treatment events, when adjusted for age at diagnosis, diagnosis, region, and first health care professional seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
69
4
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 14 publications
8
69
4
7
Order By: Relevance
“…Studies from countries with large land areas have suggested that delay is associated with the nature of the first healthcare contact, independent of distance from treatment centers [1,7,15], but our findings suggest this association could also be mediated by decision processes in the healthcare consult. Detection of symptoms and suspicion of malignancy may vary with clinical practice, making one healthcare provider more or less likely to detect and investigate for cancer.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Studies from countries with large land areas have suggested that delay is associated with the nature of the first healthcare contact, independent of distance from treatment centers [1,7,15], but our findings suggest this association could also be mediated by decision processes in the healthcare consult. Detection of symptoms and suspicion of malignancy may vary with clinical practice, making one healthcare provider more or less likely to detect and investigate for cancer.…”
Section: Discussioncontrasting
confidence: 68%
“…This association may be explained by the varying mass effect of different tumors depending on site and age, making one tumor more or less easily detected. Older children may have their health-related issues monitored less closely by parents, and may be more reluctant to disclose symptoms [7,12,13]. In addition, biologic factors may vary with age, resulting in differences in intrinsic tumor behavior [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, and survival 24,[26][27][28][29] , there is some evidence that these socioeconomic disparities also reflect poor spatial access to screening, diagnosis, and treatment 6,7,24,[30][31][32][33] . In order to provide more geographically equitable access to treatment in British Columbia (BC), Canada, the British Columbia Cancer Agency has established five new comprehensive cancer treatment centers since 1995, in addition to the original BC Cancer Centre in the city of Vancouver.…”
mentioning
confidence: 99%